2009
DOI: 10.4049/jimmunol.0901663
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: HLA-DM Functions through a Mechanism That Does Not Require Specific Conserved Hydrogen Bonds in Class II MHC-Peptide Complexes

Abstract: HLA-DM catalyzes peptide dissociation and exchange in class II MHC molecules through a mechanism that has been proposed to involve the disruption of specific components of the conserved hydrogen bond network in MHC-peptide complexes. HLA-DR1 molecules with alanine substitutions at each of the six conserved H- bonding positions were expressed in cells, and susceptibility to DM catalytic activity was evaluated by measuring the release of CLIP. The mutants αN62A, αN69A, αR76A, and βH81A DR1 were fully susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 29 publications
3
61
1
Order By: Relevance
“…In light of these observations, our data suggest that the presence of equimolar or higher concentrations of exchange peptide promotes a short-lived intermediate involving the MHC IIprebound peptide complex and the exchange peptide. An enhanced DM activity toward complexes unable to form the H-bonds between the peptide main chain at the N terminus and MHC residues a51-53 may indicate that one or more of these interactions are disrupted in the state recognized by DM (5,11). DM binds this intermediate and puts the MHC II molecule in an exchangeable conformer, promoting a widescale disruption of the interactions throughout the binding groove and an extremely rapid (noncooperative) release of the prebound peptide.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these observations, our data suggest that the presence of equimolar or higher concentrations of exchange peptide promotes a short-lived intermediate involving the MHC IIprebound peptide complex and the exchange peptide. An enhanced DM activity toward complexes unable to form the H-bonds between the peptide main chain at the N terminus and MHC residues a51-53 may indicate that one or more of these interactions are disrupted in the state recognized by DM (5,11). DM binds this intermediate and puts the MHC II molecule in an exchangeable conformer, promoting a widescale disruption of the interactions throughout the binding groove and an extremely rapid (noncooperative) release of the prebound peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Because the immunogenicity of epitopes after infection and vaccination is strongly linked to their relative DM susceptibility (8,13,58,59), understanding these determinants is crucial to follow immune responses, improve vaccines, and understand the etiology of autoimmune disease. Previous models for predicting DM susceptibility have variously implicated particular conserved hydrogen bonds near pocket 1 (17,18,20,21), spontaneous dissociation of the peptide N terminus (22,60), conformational lability of the 3 10 helical region adjacent to pocket 1 (23), an SDS-sensitive flexible conformation determined by pocket 1 occupancy (28,45), and an "compare-exchange-pushoff" mechanism (25). Although these different approaches have generally implicated interactions around the pocket 1 region (61), some studies are consistent with more distributed effects (16,25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies proposed that DM targets the conserved hydrogen bonds between MHCII and peptide in the vicinity of the P1 pocket (17,18), although others found that these interactions are dispensable for DM action (20,21,23,27). Peptide side chain pocket interactions also have been implicated in DM susceptibility, particularly emphasizing the importance of pocket 1 near the N terminus of the bound peptide (22,28).…”
Section: Antigen Presentation To Cd4mentioning
confidence: 99%
“…The mechanism by which DM mediates these effects has received much attention (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Peptides are released by DM with different rates (18), with DM susceptibility a major factor in whether or not a particular peptide is recognized by the cellular immune system (19)(20)(21).…”
mentioning
confidence: 99%